Effect of vermicompost on Gros Michel banana (Musa AAA) development in greenhouse - Vargas-Sarmiento, Frank (2025)
Introduction. From its initial stage, banana cultivation requires high-quality inputs for development and growth. The use of high-quality substrates, such as vermicompost, not only prevents the spread of soil diseases, but also promotes better development, which could help reduce production costs. Objective. To evaluate the effect of vermicompost on the growth and development of banana plants cv. Gros Michel (Musa AAA) in nursery stage. Materials and methods. At the Atlantic Campus of the Universidad de Costa Rica, located in Turrialba, Costa Rica, between July and September 2022, substrates were prepared with two types of vermicompost (anticipated [A] and delayed [P]) in doses of 0 %, 10 %, 25 % and 30 %. In vitro plants of Gros Michel banana (Musa AAA) in IV phase were then planted. Plant height, leaf area, number of leaves, leaf emission and pseudostem diameter were evaluated every two weeks. Corm diameter, fresh and dry biomass were analyzed at the beginning and end of the trial. Results. Vermicompost was beneficial at the lowest dose tested (10 % A and 10 % P). In the absence of vermicompost (0 %), plants showed the lowest development, while at the highest doses (30 % P), a phytotoxic effect was observed. Conclusion. Vermicompost stimulated banana plant growth based on the physiological variables evaluated compared to the treatment without vermicompost.